Решите (3m+4)(3m-+5)^2=-11 (6x+1)^2-(6x-1)^2=0 (4-5p)^2=(3-5p)^2-3

Jefry228 Jefry228    3   17.07.2019 05:20    0

Ответы
zeralskaya zeralskaya  03.10.2020 06:13
(3m+4)(3m-4)-(3m+5)^2=-11
(3m)^2-4^2-(3m+5)^2=-11
9m^2-16-(9m^2+30m+25)=-11
9m^2-16-9m^2-30m-25=-11
-30m-41=-11
-30m=-11+41
-30m=30
m=30/(-30)
m=-1.
(6x+1)^2-(6x-1)^2=0
((6x+1)-(6x-1))*((6x+1)+(6x-1))=0
(6x+1-6x+1)*(6x+1+6x-1)=0
2*12x=0
24x=0
x=0/

(4-5p)^2=(3-5p)^2-3
(4-5p)^2-(3-5p)^2=-3
((4-5p)-(3-5p))*((4-5p)+(3-5p))=-3
(4-5p-3+5p)*(4-5p+3-5p)=-3
1*(7-10p)=-3
7-10p=-3
-10p=-3-7
-10p=-10
p=-10/(-10)
p=1.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра